2019
DOI: 10.1515/jpm-2019-0261
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the routine first-trimester antenatal screening program for aneuploidy in the assessment of the risk of placenta accreta spectrum disorders

Abstract: AbstractObjectiveTo select a group at high risk of placenta accreta spectrum disorders (PAS) based on the data of serum screening in the first trimester.MethodsA retrospective analysis of 48 patients with abnormal placental location (AP), including placenta previa (PP) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Penzhoyan et al found a significant correlation ( p <0.15) between the PAPP-A and the blood loss volume (PAPP-P M?M was 1.37 ± 1.20 in the not higher than 1,000 mL (LBL) subgroup and 1.91 ± 1.24 in the higher than 1,000 mL (HBL) subgroup MoM indicators, p = 0.091). This research revealed that the PAPP-A level in the first trimester may be helpful for the early prognosis of pathological blood loss at delivery for pregnant women with PAS and for forming a high-risk group for PAS ( 15 ). Hence, PAPP-A plays an important role in identifying high-risk population for PAS.…”
Section: Biomarkersmentioning
confidence: 95%
“…Penzhoyan et al found a significant correlation ( p <0.15) between the PAPP-A and the blood loss volume (PAPP-P M?M was 1.37 ± 1.20 in the not higher than 1,000 mL (LBL) subgroup and 1.91 ± 1.24 in the higher than 1,000 mL (HBL) subgroup MoM indicators, p = 0.091). This research revealed that the PAPP-A level in the first trimester may be helpful for the early prognosis of pathological blood loss at delivery for pregnant women with PAS and for forming a high-risk group for PAS ( 15 ). Hence, PAPP-A plays an important role in identifying high-risk population for PAS.…”
Section: Biomarkersmentioning
confidence: 95%
“…Table 1 summarizes the characteristics of the studies included in the meta-analysis. In general, 7 retrospective studies [17,18,[20][21][22][23][24] and one prospective study, [19] consisting of 243 pregnant women with PAS and 1599 pregnant women without PAS, were available for the subsequent meta-analysis. These studies were conducted in the United States, the United Kingdom, Turkey, Russia, and China between 2014 and 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean ages of the included women were 30 to 35 years. The diagnosis of PAS was histologically validated in 7 studies [17,[19][20][21][22][23][24] and confirmed by the medical records in one study. [18] First-trimester serum PAPP-A levels were measured with an immunoassay for all included studies and reported as multiples of median (MoM) values.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…First trimester pregnancy-associated plasma protein A (PAPP-A) and second trimester alpha-fetoprotein (AFP) are higher in women with PAS [2,71,72]. Low first trimester and high second trimester human chorionic gonadotropin (HCG) has been inconsistently associated with PAS [2,71,73,74]. Although these abnormal serum markers may strengthen the suspicion for PAS, their positive predictive values are not high.…”
Section: Biomarkersmentioning
confidence: 99%